A structured technique for applying Risk Based Internal Auditing in information technology environments (with specific reference to IIA RBIA, King Report and CobiT) - Wheeler, Sonya (Stellenbosch : University of Stellenbosch, 2008)
Thesis (M.Comm. (Accountancy))--University of Stellenbosch, 2005.